Measures of another gaze... About the materiality of the space of daycare centers and the constitution of a place for infants - Luciane Pandini Simiano (Arizona State University, 2014)
This article focuses on the configuration of the space of daycare centers as a place for babies. This is a research project with an ethnographic orientation, conducted in a public daycare center in the Southern part of Santa Catarina. The research focused on ten babies, four adults group, two teachers and two assistants. This research advocates for the importance of organizing the space for babies, because space educates, exposes ideas, and provides messages. The building, furniture, objects and their organization potentiate or hinder learning. It is necessary, however, to go beyond the materiality. It is essential to look, recognize, and value forms of use of space and the meanings developed between babies and adults. In the experiences in the time of meetings and breaks, spaces are constituted and constitutive. That is another form of looking about being and using a daycare center.